Weak localization and the approach to metal–insulator transition in single crystalline germanium nanowires. (7th February 2017) - Sett, Shaili; Das, K; Raychaudhuri, A K
Abstract: We study the low-temperature electronic transport properties of single germanium nanowires (NWs) with diameters down to 45 nm to investigate the weak localization (WL) behavior and approach to metal–insulator transition (MIT) within them. The NWs (single crystalline) we investigate lie on the metallic side of the MIT with an extrapolated zero temperature conductivity σ 0 in the range 23 to 1790 ( Ω cm) −1 and show a temperature-dependent conductivity which below 30 K can be described by a 3D WL behavior with Thouless length L T h ∼ T − p 2 and p ∼ 4 . From the observed value of σ 0 and the value of the critical carrier concentration n c, it is observed that the approach to MIT can be described by the scaling equation σ 0 ∼ ( n − n c ) ν with ν ≈ 0.6, which is a value expected for an uncompensated system. The investigation establishes a NW size limit for the applicability of 3D scaling theories.